Hepato-biliary transport of immunoglobulin in the antarctic teleost Trematomus bernacchii. - ABELLI, Luigi; ZENI, Cristina; Coscia M. R.; De Santis A.; Oreste U. (2004)
Presence of immunoglobulins (Ig) in the liver of Trematomus bernacchii was investigated by biochemical and immunochemical assays with polyclonal antisera raised in rabbits against purified T. bernacchii serum Ig heavy (IgH) and light chains (IgL). Bile Ig were quantified by ELISA (4.1 mg/ml) and purified. Western blot analysis of SDS-PAGE separated bile proteins, performed using IgH- or IgL-specific antisera, revealed two IgH bands (76 and 66 kDa) and the IgL band (25 kDa). Similar results were obtained when extracted liver proteins were analysed by the same method. SDS-PAGE under non-reducing conditions of bile proteins revealed multiple bands (ranging from 200 to 830 kDa) resulting from different Ig polimerization forms. Finally, IEF analysis of the bile Ig showed a wide range of pI values. Immunohistochemistry detected IgH- and IgL-reactivity in the plasma of hepatic sinusoids, in cells extravasated in the perisinusoidal space, in bile canaliculi and pre-ductules. These findings strongly indicate that Ig, derived from blood and/or activated B-cells, could be transported across the hepatocytes to be secreted into the bile. In the anterior intestine, the intraluminal mucus retained a significant Ig-immunoreactivity, while the mucosa housed a limited density of Ig-bearing cells. In addition, extravasated plasma cells accumulated within identifiable portal tracts and close to the liver capsule that, in turn, was evenly coated by Ig molecules at the peritoneal surface. These peculiar features could be explained in light of liver defence system against ascending infections and/or colonization by nematode parasites and suggest that the Ig could protect the intestinal epithelium via the hepato-biliary transport route.